2018
DOI: 10.1139/cjce-2018-0049
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study of reinforced concrete interior wide beam-column joints subjected to lateral load

Abstract: Past researches showed that the energy dissipation capacity of the wide beam-column joints was not sufficient. So, two full-scale reinforced concrete interior wide beam-column joints were tested under quasi-static cyclic loads and the performance of the specimens was studied experimentally and numerically. Effect of using wide beams in two directions was investigated and it became clear that the longitudinal reinforcement of transverse wide beam had significant effect on the seismic behavior of the joints. Fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Balok lebar memiliki inersia rendah sehingga desainnya memerlukan tulangan yang besar untuk memikul momen yang bekerja. Hal ini membuat desain kolom juga berpengaruh terkait dengan aturan kolom kuat balok lemah, walaupun secara kekakuan telah memenuhi persyaratan (Benavent-Climent, 2007;Climent et al, 2008;Fadwa et al, 2014;Mirzabagheri et al, 2018). Pengamatan secara numerical menunjukkan peningkatan mutu beton tidak memberikan pengaruh significant pada join balok lebarkolom (Mirzabagheri et al, 2018).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Balok lebar memiliki inersia rendah sehingga desainnya memerlukan tulangan yang besar untuk memikul momen yang bekerja. Hal ini membuat desain kolom juga berpengaruh terkait dengan aturan kolom kuat balok lemah, walaupun secara kekakuan telah memenuhi persyaratan (Benavent-Climent, 2007;Climent et al, 2008;Fadwa et al, 2014;Mirzabagheri et al, 2018). Pengamatan secara numerical menunjukkan peningkatan mutu beton tidak memberikan pengaruh significant pada join balok lebarkolom (Mirzabagheri et al, 2018).…”
Section: Pendahuluanunclassified
“…Hal ini membuat desain kolom juga berpengaruh terkait dengan aturan kolom kuat balok lemah, walaupun secara kekakuan telah memenuhi persyaratan (Benavent-Climent, 2007;Climent et al, 2008;Fadwa et al, 2014;Mirzabagheri et al, 2018). Pengamatan secara numerical menunjukkan peningkatan mutu beton tidak memberikan pengaruh significant pada join balok lebarkolom (Mirzabagheri et al, 2018). Penggunaan balok lebar pada struktur rangka penahan momen yang diaplikasikan memberikan keuntungan tetapi juga kerugian.…”
Section: Pendahuluanunclassified
“…Various researchers did numerical modelling of reinforced concrete structures because of its power in studying various types of structures [13,14] . However, it is strongly suggested that experimental results be used to validate computer models and then the validated models be used to simulate the behaviour of structures.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most popular smeared crack concrete models is the concrete damage plasticity model (CDP), proposed by Lubliner et al [29], developed by Lee and Fenves [30], and implemented in ABAQUS [31]. Because of the high computational cost of nonlinear analysis of RC structures, especially for fine mesh sizes between 25 mm and 12.5 mm [32][33][34], many researchers [35][36][37][38][39][40] successfully obtain the detailed behaviors of different structural elements tested under cyclic loading (i.e., load-displacement backbone curves, cracking patterns, yielding in reinforcement bars) by adopting monotonic loads through the CDP model. On the other side, several researchers [41][42][43][44][45][46] failed to obtain the cyclic characteristics of different structural responses for elements modeled via CDP even at a 30 mm mesh element size [47].…”
Section: Introductionmentioning
confidence: 99%